Panorama Eksistensi Kesadaran Cogito Ergo Sum menuju Cogito Ergo Zoom dalam Pembelajaran Online - Alfredo Kevin; Fransiskus Armada Riyanto (Jurnal Filsafat Indonesia, 2022)
The study of this article gave attention to the panoramic scheme of new thinking patterns in education during a pandemic. The methodology used in the study is qualitative-descriptive. The theme raised by the author is postmodern Cartesian metaphysics about the concept of thinking in determining an awareness of human existence. The discussion contains an elaboration of thinking activities in learning through the Zoom learning application and Rene Descartes’ famous philosophy of “Cogito Ergo Sum”. Understanding the Cartesian method always doubts everything that is visible to the senses. The purpose of writing is to explore the influence of online classroom situations in human thinking processes to achieve scientific certainty in front of a spectral screen. Knowledge is mindful awareness. The reality of Zoom’s current effectiveness creates a paradox. Online learning creates an interactive space but on the other it also has an impact on creating a saturate space in learning so that it affects the awareness of human thinking to achieve knowledge. The author finds a shift in the important meaning of Descartes’ “Cogito Ergo Sum” to “Cogito Ergo Zoom”. This is inseparable from the dependence of the current pattern of human thinking on networks system and spectral screens.